Sulfonamide-supported group 4 catalysts for the ring-opening polymerization of epsilon-caprolactone and rac-lactide. - Schwarz, A; Thompson, A; Mountford, P (2009)
Reaction of RCH(2)N(CH(2)CH(2)NHSO(2)Tol)(2) (R = 2-NC(5)H(4) (8, H(2)L(py)) or MeOCH(2) (9, H(2)L(OMe))) with Ti(NMe(2))(4) at room temperature afforded Ti(L(py))(NMe(2))(2) (10) or Ti(L(OMe))(NMe(2))(2) (11), respectively, which contain tetradentate bis(sulfonamide)amine ligands. The corresponding reactions with Ti(O(i)Pr)(4) or Zr(O(i)Pr)(4) x HO(i)Pr required more forcing conditions to form the homologous bis(isopropoxide) analogues, M(L(R))(O(i)Pr)(2) (M = Ti, R = py (12) or OMe (14); M = Zr, R = py (13) or OMe (15)). Reaction of Ti(NMe(2))(2)(O(i)Pr)(2) with H(2)L(R) formed 12 or 14 under milder conditions. The X-ray structures of 10-15 have been determined revealing C(s) symmetric, 6-coordinate complexes except for 13 which is 7-coordinate with one kappa(2)(N,O) bound sulfonamide donor. Compounds 10-15 are all catalysts for the ring-opening polymerization (ROP) of epsilon-caprolactone, with the isopropoxide compounds being the fastest and best controlled, especially in the case of zirconium. In addition, Zr(L(OMe))(O(i)Pr) (2) (15) was an efficient catalyst for the well-controlled ROP of rac-lactide both in toluene at 100 degrees C and in the melt at 130 degrees C, giving atactic poly(rac-lactide). The polymerization rates and control achieved for 13 and 15 are comparable to those of the well-established bis(phenolate)amine-supported Group 4 systems reported recently.